County Population Estimates (Experimental) by Age, Sex, and Race: 1980-1985 ([Verlag nicht ermittelbar], 1990)
This dataset contains county population estimates for July 1, 1980 through 1985. Estimates are provided by age (18 age groups), sex, and race (White, Black, and other races). These estimates make full use of 1980 Census data on gross in- and out-migration for counties. The data are considered experimental, and replace estimates labeled "provisional." Because the data were originally prepared for the National Cancer Institute (NCI) they are sometimes referred to by that name.